Unloading-Induced Crack Propagation of Two Collinear Unequal Length Flaws in Brittle Rocks. (5th June 2020) - Wang, Jianming; Chen, Zhonghui; Zhang, Lingfan
Abstract : The propagation and coalescence of numerous discontinuous joints significantly contribute to landslide instability during excavation unloading. The tip expression of stress intensity factors of two collinear unequal length cracks in a typical rock mass under unloading conditions was calculated based on the superposition principle and fracture mechanics to determine the meso-influence law of intermittent joint interaction in the slope under the action of excavation. The effects of many factors on this interaction were also analyzed theoretically. Unloading tests were conducted on rock-like specimens with two collinear unequal length cracks in addition to numerical simulation and theoretical analysis. The results show decreased interaction between the two cracks with increased crack distance, increased influence of the main crack on a secondary crack with increased length of the main crack, and decreased influence of the secondary crack on the main crack with decreased length of the secondary crack. Wing tensile cracks first appear at the tip of flaws, and the propagation of these cracks occurs with the generation of secondary tensile cracks and shear cracks during unloading. Propagation and coalescence between cracks lead to tension and shear mixed failure of a rock bridge, and tensile cracks appear near the unloading surface. The axial initiation and peak stress of a crack increase with increased flaw distance, and the theoretical calculations were confirmed by lateral unloading test results.